Economic Feasibility and Market Viability Analysis of Rehabilitation Exoskeleton Development for Stroke Recovery in Indonesia - Muchammad Haidar Afif,; Silvi Istiqomah,; Dominggo Bayu Baskara,; Dimas Adiputra, (IPTEK The Journal for Technology and Science, 2026)
This paper evaluates the feasibility and market viability of a domestically produced rehabilitation exoskeleton in Indonesia. The research incorporates a comprehensive economic analysis, including Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP) to determine the investment potential of different production models: factory construction, building rental, and factory purchase. The findings indicate that while renting a building may yield a high IRR, the negative PP suggests a lack of long-term asset accumulation, making it unsustainable. Meanwhile, factory construction and purchase offer stronger long-term economic benefits. Additionally, market analysis highlights the cost advantage of the locally developed exoskeleton compared to imported models, with a 75%-85% price reduction, making it significantly more accessible for patients and medical institutions. The domestic production strategy not only reduces import dependency but also ensures adaptability to local patient needs, positioning the exoskeleton as a highly viable and impactful medical technology for Indonesia’s rehabilitation sector.